A Dual world economy forty years of development experience - Adriaansen, W. L. M.; Waardenburg, J. George (Bombay Oxford University Press, 1992)
Contributed articles.
Includes bibliographical references.
Includes index.
Keywords: Economic history -- 1945-; Income distribution; Developing countries -- Economic conditions